Pengembangan Buku Pop Up Untuk Kegiatan Bercerita Anak di PAUD Bougenville - Ridhagitha Kurnia; Retno Widyaningrum; Diana Ariani (Universitas Negeri Jakarta, 2019)
This development research aims to create product in the form of pop up story books. This book is a learning medium that is used for storytelling activities in a Play Group named Bougenville. This development research was carried out by following the Baker & Schutz development model, which consist of 1) Formulation, 2) Instructional Specification, 3) Item Tryout, 4) Product Development, 5) Product Tryout, 6) Product Revision, and 7) Operation Analysis. The product evaluation is done through Expert Review and Field Test. The expert review phase involves 1 subject matter expert and 1 media expert. The average score obtained from experts review is 3.7 which considered as very good. For field test, the pop up story book has tested on 15 students, The average score obtained at this phase is 88% which considered as good. So, it can be concluded, this development research has created an Animal Theme Pop Up Book which used for storytelling activities in Bougenville Play Group.